Anthocyanins Prevent Colorectal Cancer Development in a Mouse Model - Lippert, Elisabeth; Ruemmele, Petra; Obermeier, Florian; Goelder, Stefan; Kunst, Claudia; Rogler, Gerhard; Dunger, Nadja; Messmann, Helmut; Hartmann, Arndt; Endlicher, Esther (Digestion, 2017)
Colorectal cancer is the main leading cause of cancer-related deaths worldwide. Present data suggest that plant-derived anthocyanins have anti-inflammatory and chemopreventive properties. This study was aimed at evaluating the effect of an anthocyanin-rich extract from bilberries on colorectal tumour development and growth in the administration of azoxymethan (AOM)/dextran sodium sulfate (DSS) mouse model.Colonic carcinogenesis was induced by AOM and DSS 3 or 5%, respectively, in 50 female Balb/c mice. Mice received either normal food (controls) or a diet containing either 10 or 1% anthocyanin-rich bilberry extract. Colonoscopy took place at week 4 and 9 after initiation of carcinogenesis. After termination at week 9, colon samples were analysed macroscopically and microscopically.Mice receiving 10% anthocyanins showed significantly (p < 0.004) less reduced colon length (12.1 cm [8.5-14.4 cm]) as compared to controls (11.2 cm [9.8-12.3]) indicating less inflammation. Mice fed with 10% anthocyanin-rich extract revealed significantly less mean tumour numbers (n = 1.2) compared to control (n = 14) and anthocyanin 1% treated mice (n = 10.6, p < 0.001).Anthocyanins prevented the formation and growth of colorectal cancer in AOM/DSS-treated Balb/c mice. Further studies should investigate the mechanisms of how anthocyanins influence the development of colorectal cancer.
EVALuna2:6869